2019
DOI: 10.1039/c8gc03447h
|View full text |Cite
|
Sign up to set email alerts
|

In situpretreatment during distillation improves corn fiber conversion and ethanol yield in the dry mill process

Abstract: The in situ pretreatment and in situ conversion of corn fiber increased cellulose conversion and the overall ethanol yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In general, almost all cellulases, except BG-Pc, showed the reduced activity in ethanol cosolvents (Figure 1a), agreeing well with our previous studies. 7,21 In detail, the residual activities of EG-An and CBHII-Hi significantly decreased as the ethanol concentration increased. Notably, the CBHII-Hi lost almost all activity (3.8% residual activity) in 16% (v/v) ethanol, indicating that the ethanol molecules forcefully inhibit the activity of CBHII-Hi.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…In general, almost all cellulases, except BG-Pc, showed the reduced activity in ethanol cosolvents (Figure 1a), agreeing well with our previous studies. 7,21 In detail, the residual activities of EG-An and CBHII-Hi significantly decreased as the ethanol concentration increased. Notably, the CBHII-Hi lost almost all activity (3.8% residual activity) in 16% (v/v) ethanol, indicating that the ethanol molecules forcefully inhibit the activity of CBHII-Hi.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Although less wastewater is produced due to biological detoxification rather than water washing and overliming, high citric acid dosage (4%) and reaction temperature (165°C) during pretreatment and too-long biodetoxification as strain growth and inactivation after detoxification influenced the economy of the process. Li et al (2019) used the combination of acid pretreatment with distillation to in situ pretreat whole stillage containing corn fiber. The pretreated stillage was recycled to the liquefaction step with the addition of cellulase, or hydrolyzed using cellulase and then recycled to the liquefaction step, or hydrolyzed using cellulase followed by C6/C5 sugar co-fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Iram et al (2019) pretreated DDGS with dilute acid, and the yield of total reducing sugar (TRS) reached 0.382 g/g DDGS; besides TRS, furfural and HMF were also produced during the acid pretreatment. Li et al (2019) used the combination of acid pretreatment with distillation to in situ pretreat whole stillage containing corn fiber and recycled it to the liquefaction step, which improved the ethanol yield by 6.3% compared to the traditional process, and the cellulose conversion was 77.5%, but similarly, many inhibitors were also produced, which led to incomplete fermentation. Noureddini and Byun (2010) used dilute sulfuric acid to treat corn fiber and found that the highest yield of monosaccharides (63.1 g sugar/100 g corn fiber) was obtained when the pretreatment was conducted at 5% of biomass loading (w/w), 1.5% of sulfuric acid concentration (v/v), and 140°C, but the concentration of furfural in pretreatment liquor was also high (3.8 mg/ml) after pretreatment under the conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although CF is mainly valorized in feeds, it can be also a useful substrate for bioethanol production [17]. Recently, intense research efforts have been made to develop novel and efficient processes for the conversion of CF into ethanol, which could highly improve the ethanol yield in a corn-to-ethanol facility [18][19][20][21]. In addition, CF could serve as a raw material for the production of other high-value bio-products beside ethanol, if it is utilized in a biorefinery process allowing the efficient and selective fractionation of valuable CF components, such as hemicellulosic sugars.…”
Section: Introductionmentioning
confidence: 99%